Histological examination of the potential arrhythmic substrates in the setting of Ebstein's malformation. Issue 1 (2nd March 2020) - Sánchez‐Quintana, Damián; Cabrera, José Angel; Picazo‐Angelin, Beatriz; Cabrera, Alberto; Anderson, Robert H.
Abstract: Cardiac arrhythmias, notably Wolff‐Parkinson‐White syndrome, are known to represent a major issue in patients with Ebstein's malformation of the tricuspid valve. Abnormal conducting circuits, however, can also be produced by pathways extending either from the atrioventricular node or the ventricular components of the atrioventricular conduction axis, direct to the crest of the muscular ventricular septum. We hoped to provide further information on the potential presence of such pathways by investigations of six autopsied examples of Ebstein's malformation. All were studied by histological sectioning on the full extent of the atrioventricular conduction axis, with limited sectioning of the right atrioventricular junction supporting the inferior and antero‐superior leaflets of the deformed tricuspid valve. We used the criteria established by Aschoff ( Verhandlungen der Deutschen Gesellschaft für Pathologie, 14, 1910, 3) and Mönckeberg ( Verhandlungen der Deutschen Gesellschaft für Pathologie, 14, 1910, 64) over a century ago to define abnormal connections across the atrioventricular junctions, as these definitions retain their validity for the identification of gross myocardial connections across the insulating tissues of the atrioventricular junctions. In one specimen, we found two discrete accessory myocardial connections across the parietal right atrioventricular junction. In all of the hearts, we found so‐called nodoventricular connections, and in one heart we also observed a well‐formed connection originating from the penetrating atrioventricular bundle. In addition to accessory myocardial connections across the parietal right atrioventricular junction, therefore, our histological findings demonstrate a potential role for direct connections between the atrioventricular conduction axis and the ventricular myocardium in the setting of Ebstein's malformation. Abstract : The sections are stained using Masson's trichrome technique with myocardial tissues coloured brown, and the insulating fibrous tissues coloured blue‐green and show abnormal connections through the insulating plane joining the base of the compact atrioventricular node to the crest of the muscular ventricular septum. These are the so‐called nodoventricular connections, and they have the potential capacity either to produce ventricular pre‐excitation or to participate in abnormal re‐entry circuits. The sections shown in these images are taken from specimen #2.